Pengujian dalam Pengambilan Keputusan Investasi Menggunakan Model Belief Adjustment dengan Pola Penyajian End of Sequence - Arvianti, Vivi Septi; Sari, Rida Perwita (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research aims to examine whether the End of Sequence presentation pattern has an influence on investment decision making using the order of evidence (good news followed by bad news and bad news followed by good news), non-complex information type (fundamental analysis) and complex information type (fundamental analysis and technical analysis). This experimental research uses a 2 x 2 factorial experimental design between designs with variables that manipulate independent variables, namely the order of information evidence and information type, and investment decisions as the dependent variable. This study used students of the Bachelor of Accounting study program at UPN